2008
DOI: 10.4049/jimmunol.180.5.2894
|View full text |Cite
|
Sign up to set email alerts
|

AIMP1/p43 Protein Induces the Maturation of Bone Marrow-Derived Dendritic Cells with T Helper Type 1-Polarizing Ability

Abstract: AIMP1 (ARS-interacting multifunctional protein 1), previously known as p43, was initially identified as a factor associated with a macromolecular tRNA synthetase complex. Recently, we demonstrated that AIMP1 is also secreted and acts as a novel pleiotropic cytokine. In this study, we investigated whether AIMP1 induces the activation and maturation of murine bone marrow-derived dendritic cells (DCs). AIMP1-treated DCs exhibited up-regulated expression of cell-surface molecules, including CD40, CD86, and MHC cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…AIMP1 is also secreted and has been shown to have various activities, including effects on wound healing (10) and glucagon-like functions that control blood glucose levels (11). Furthermore, we demonstrated that AIMP1 functions as a proinflammatory cytokine that induces macrophage activation, DC maturation, and IL-12 production, indicating that AIMP1 is a novel immune modulator (12,13). However, it is unclear whether AIMP1 affects other APCs, such as B cells.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…AIMP1 is also secreted and has been shown to have various activities, including effects on wound healing (10) and glucagon-like functions that control blood glucose levels (11). Furthermore, we demonstrated that AIMP1 functions as a proinflammatory cytokine that induces macrophage activation, DC maturation, and IL-12 production, indicating that AIMP1 is a novel immune modulator (12,13). However, it is unclear whether AIMP1 affects other APCs, such as B cells.…”
mentioning
confidence: 85%
“…The in vivo administration of AIMP1 induced CD69 expression on splenic B cells, indicating that AIMP1 is a critical B cell activator. We previously reported that AIMP1 activates macrophages and DCs (12,13). Because stimulated macrophages and DCs are known to express BAFF and APRIL (18), the in vivo data might be, at least in part, mediated by these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). Although AIMP1 is mainly bound to the multi-tRNA synthetase complex, it is also secreted on hypoxia or cytokine stimulation and works as a cytokine on various target cells such as endothelial cells, monocyte/macrophage, dendritic cells (DCs), fibroblasts, and pancreatic a cells (23)(24)(25)(26)(27)(28). The secreted AIMP1 controls angiogenesis depending on its local concentration.…”
Section: Structure and Regulatory Functions Of Aimp1mentioning
confidence: 99%